Edukasi Pelajar Tentang Bahaya Merokok Bagi Kesehatan - Mufida, Mufida; Rabiah, Rabiah; Tuti, Muslimah; Damayanti, Finda; Vista, Nadia; Asril, Kiki Cahyani; Nusi, Olivia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Smoking is on of the main risk factors for several chronic diseases that can lead to death. This shows that smoking is a big problem for public health perspective, smoking also affects the personality of the smoker himself. Usually junior high school age teenagers are familiar with smoking. The background to this counseling activity is that there are still many teenagers in their surrounding who smoke. The method used in the carrying out health education activities is by holding offline-based counseling at MTS Nurul Islam Tawaeli on Tuesday, agustus 2023 in the city of palu, central Sulawesi. The counseling is carried out using the presentation and question and answer. Shows that 85,4% respondens in this study already had good knowledge about the dangers of smoking to health. But there were still 3 respondents who had less knowledge about the dangers of smoking to health. Shows that there is an increase in adolescent knowledge before and after being given counseling about the danger of smoking to health online. It can be interpreted that teenagers at MTS Nurul Islam Tawaeli already have good knowledge about the dangers of smoking to healt and are expected to be able to apply and disseminate the information they get to friends and family at home. More than half of teenagers have low knowledge about the dangers of smoking.